2017
DOI: 10.1080/17429145.2017.1392624
|View full text |Cite
|
Sign up to set email alerts
|

Root interactions and tomato growth in tomato/potato onion companion-cropping system under different phosphorus levels

Abstract: When two plants interact, changes in plant growth are usually related to variations in root distribution and phosphorus (P) levels. However, root distributions and root tendencies are difficult to study because root systems grow beneath the soil surface. In this study, a transparent root box was used to observe interactions between root systems in situ, and the relation between tomato growth and root proliferation at different depths and distance from the rows at no P added and 120 mg kg-1 P added levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
1
9
0
2
Order By: Relevance
“…Potato-onion ( Allium cepa L. var. aggregatum G. Don), a variant of onion, has been regarded as a promising intercropping plant by some researchers, especially the variety “Suihua”, which has shown stronger positive effect in diversified cropping systems [ 14 , 15 ]. In our previous studies, we found that the tomato/potato-onion intercropping system was a diversified cropping system with multiple agro-ecological functions, such as alleviating the incidence and severity of tomato verticillium wilt [ 16 ], increased the community structure and function of phosphobacteria in tomato rhizosphere, and promoted the P uptake of tomato [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Potato-onion ( Allium cepa L. var. aggregatum G. Don), a variant of onion, has been regarded as a promising intercropping plant by some researchers, especially the variety “Suihua”, which has shown stronger positive effect in diversified cropping systems [ 14 , 15 ]. In our previous studies, we found that the tomato/potato-onion intercropping system was a diversified cropping system with multiple agro-ecological functions, such as alleviating the incidence and severity of tomato verticillium wilt [ 16 ], increased the community structure and function of phosphobacteria in tomato rhizosphere, and promoted the P uptake of tomato [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we found that potato onion is an effective partner for intercropping and relay intercropping. Intercropping with potato onion increased the growth of tomato seedlings and changed tomato root architecture (Wu et al 2016;Yu et al 2017) and the root exudates of potato onion has facilitating effects on tomato seedlings (Liu et al 2013). To date, however, the effects of potato onion leaf volatiles and leachates have remained virtually unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our previous study has demonstrated that the belowground interactions between potato onion and tomato can change the root architecture of tomato (Yu et al 2017), whereas comparatively little consideration has been given to the aboveground interactions between the two plants. In the present study, we therefore aimed to explore the effects of the volatiles and leachates of potato onion leaves on tomato growth, and compared the gene expression profiles of two potato onion cultivars with different facilitating potentials in a potato onion/tomato intercropping system.…”
Section: Introductionmentioning
confidence: 99%
“…Companion crop juga dapat disebut sebagai tumpang sari tanaman pakan dan pangan yang diharapkan mampu menekan gulma, meningkatkan kesuburan tanah, mengurangi erosi dan meningkatkan pemanfaatan sumber daya (air, cahaya, dan nutrisi). Sistem companion crop telah lama digunakan untuk meningkatkan produktivitas tanaman dan keunggulan biomassa dalam pertanian modern (Yu et al, 2017). Tanaman yang digunakan untuk mengisi ruang kosong rumput odot harus memiliki tinggi tajuk yang tidak lebih dari tanaman odot, karena untuk menghindari terjadinya persaingan dalam mendapatkan cahaya matahari.…”
Section: Pendahuluanunclassified